Balanced centricity and triads: strategies to reach ecosystem equilibrium in the arts sector. Issue 3 (21st November 2019) - Quero Gervilla, María José; Díaz-Mendez, Montserrat; Gummesson, Evert
Abstract : Purpose: The purpose of this paper is to analyze whether triad structures, as the smallest unit of a network, can facilitate or inhibit the evolution into a service ecosystem. According to SD logic literature, the triad structure and the institutions that dominate the triads determine the evolution into ecosystem, remain as triad or die. "Balanced centricity" is considered a desirable institution that increases the possibility of transforming triads into ecosystems through marketing equilibrium. Design/methodology/approach: The authors apply a conceptual approach to develop a framework for deepening understanding about triads' structures from the institution's perspective (balanced centricity). Qualitative case study research was conducted using different methods of data generation including personal interviews and netnography analysis in the arts sector. Three case studies were developed, one for each triad structure: Sothebýs, Patreon and Vibuk. Findings: New business models start being a triad, and it is a strategic option to evolve into an ecosystem. In this sense, authors argue for considering balanced centricity as an institution that enables the ecosystems to arise. From this perspective, balanced centricity can be considered a strategy that helps to balance and reach positive relationships among actors, enabling the process to become a "balance triad structure". Research limitations/implications: The paper is a conceptual work that combines with an empirical approach. The empirical approach considers three success cases on the arts context. Considering other contexts as different from arts industry would be useful to add new perspectives to the theory development. Originality/value: The present paper defines a new form of triad "balanced triad structure" (BTS) and identifies categories depending on the way balanced centricity institution is adopted, facilitating or inhibiting the future evolution into an ecosystem. Hitherto, previous papers have not put together these concepts that build on the triads and ecosystems theory to better understand triads management and facilitate the evolution of three-actor networks into ecosystems.